Kebugaran Jasmani: Permainan Tradisional Sebagai Warisan Budaya - Alif Tunru, Andi; Hidayat, Rachmat; Syarif Burhan, Ahmad (Pendas Mahakam : Jurnal Pendidikan dan Pembelajaran Sekolah Dasar, 2024)
Traditional games are forms of play or sports activities that possess unique regional characteristics and are adapted to local cultural traditions. The study aims to determine whether traditional games, as a cultural heritage, influence the improvement of physical fitness among students aged 10-12 years at SDN 024 Samarinda Utara. The research results indicate a significant influence of the traditional game gobak sodor on improving physical fitness among students aged 10-12 years at SDN 024 Samarinda Utara. The conclusion is that incorporating traditional games into the physical education curriculum can serve as an effective strategy for enhancing students' overall health and physical fitness.